Reform of the International Monetary System : A Jagged History and Uncertain Prospects - Lin, Justin Yifu (World Bank, Washington, DC, 2012)
This paper analyzes the historical evolution of the international monetary system in the context of the rising role of developing countries in the world economy and the emerging multi-polar growth setting. It evaluates the stability of the current "non-system" and how the global economic context is likely to affect that stability in the coming years with potential adverse effects on both advanced and developing economies. Given the likely trend toward a multi-polar reserve currency system, the paper evaluates the stability of the emerging system, as well as the current proposals for reform of the international monetary system. The paper concludes that more ambitious reforms of the system may be needed to meaningfully reduce future global economic and financial instability.